Nematosit pada Tiga Spesies Karang Scleractinia, Acropora formosa, Seriatopora sp, dan Pocillopora damicornis Di Pantai Nirwana Sumatera Barat - Khairunnisa Gunawan; Thamrin Thamrin; Syafruddin Nasution (Pelantar Press, 2023)
This research was carried out in July - August 2022. The location of coral sampling is in the coral reefs of the Nirwana coast, West Sumatra. The objective by conducting this study is to determine the type of nematocysts in the body tissues of corals scleractinia, Acropora formosa, Seriatopora sp, and Pocillopora damicornis. Method to know the types of nematocysts from A. formosa, Seriatopora sp, and P. damicornis were carried out using an Olympus, microscope with x100 objective lens magnification at the Marine Biology Laboratory, Faculty of Fisheries and Marine Science, University of Riau. Of the 25 major types of nematocysts known in the phylum Cnidarian, two types are found in these three species. The results showed that there were two main types of nematocysts, namely holotrichous isorhizas (HI) and micro basic p-mastigophore (MpM). The three coral species, A. formosa, Seriatopora sp, and P. damicornis, of the holotrichous isorhizas (HI) nematocysts type and the micro basic p-mastigophore (MpM) nematocyst, were found in the coral species A. formosa and P. damicornis. The type of nematocyst is thought to be used to attack and kill prey.